Mammary and extramammary Paget's disease - Lauro Lourival Lopes Filho; Ione Maria Ribeiro Soares Lopes; Lauro Rodolpho Soares Lopes; Milvia M. S. S. Enokihara; Alexandre Osores Michalany; Nobuo Matsunaga (Sociedade Brasileira de Dermatologia, 2015)
Paget's disease, described by Sir James Paget in 1874, is classified as mammary and extramammary. The mammary type is rare and often associated with intraductal cancer (93-100% of cases). It is more prevalent in postmenopausal women and it appears as an eczematoid, erythematous, moist or crusted lesion, with or without fine scaling, infiltration and inversion of the nipple. It must be distinguished from erosive adenomatosis of the nipple, cutaneous extension of breast carcinoma, psoriasis, atopic dermatitis, contact dermatitis, chronic eczema, lactiferous ducts ectasia, Bowen's disease, basal cell carcinoma, melanoma and intraductal papilloma. Diagnosis is histological and prognosis and treatment depend on the type of underlying breast cancer. Extramammary Paget's disease is considered an adenocarcinoma originating from the skin or skin appendages in areas with apocrine glands. The primary location is the vulvar area, followed by the perianal region, scrotum, penis and axillae. It starts as an erythematous plaque of indolent growth, with well-defined edges, fine scaling, excoriations, exulcerations and lichenification. In most cases it is not associated with cancer, although there are publications linking it to tumors of the vulva, vagina, cervix and corpus uteri, bladder, ovary, gallbladder, liver, breast, colon and rectum. Differential diagnoses are candidiasis, psoriasis and chronic lichen simplex. Histopathology confirms the diagnosis. Before treatment begins, associated malignancies should be investigated. Surgical excision and micrographic surgery are the best treatment options, although recurrences are frequent.